2014
DOI: 10.1007/s00442-014-3014-7
|View full text |Cite
|
Sign up to set email alerts
|

Habitat fragmentation, tree diversity, and plant invasion interact to structure forest caterpillar communities

Abstract: Habitat fragmentation and invasive species are two of the most prominent threats to terrestrial ecosystems. Few studies have examined how these factors interact to influence the diversity of natural communities, particularly primary consumers. Here, we examined the effects of forest fragmentation and invasion of exotic honeysuckle (Lonicera maackii, Caprifoliaceae) on the abundance and diversity of the dominant forest herbivores: woody plant-feeding Lepidoptera. We systematically surveyed understory caterpilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 83 publications
2
10
0
Order By: Relevance
“…We have previously referred to the intermediate disturbance hypothesis and its suggestions that plant and Lepidoptera diversity and/or abundance could peak in disturbed habitats if they exhibit moderate levels of disturbance and thereby possess a mix of both early and late successional species [ 3 , 8 ], and/or edge and interior specialist species [ 53 ], and/or native and exotic species [ 39 , 40 ]. We cannot conclusively test or demonstrate this because, as discussed above, disturbance is so widespread that we lack a good frame of reference for undisturbed habitats in the region.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously referred to the intermediate disturbance hypothesis and its suggestions that plant and Lepidoptera diversity and/or abundance could peak in disturbed habitats if they exhibit moderate levels of disturbance and thereby possess a mix of both early and late successional species [ 3 , 8 ], and/or edge and interior specialist species [ 53 ], and/or native and exotic species [ 39 , 40 ]. We cannot conclusively test or demonstrate this because, as discussed above, disturbance is so widespread that we lack a good frame of reference for undisturbed habitats in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have produced nuanced and sometimes mixed results regarding the effects of anthropogenic habitat modification on Lepidoptera communities. Most studies have found that, although some Lepidoptera species benefit, human impacts are generally detrimental to more species and to overall Lepidoptera richness, abundance, and diversity [3,23,[37][38][39][40]. However, some studies have documented positive effects of human impacts of Lepidoptera communities, for example, when introduced vegetation provides more attractive nectar sources and can cause host plant switches in butterflies [23].…”
Section: Rationale and Related Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…30 Separately, honeysuckle was found to cause a decrease in caterpillar abundance that was moderated when there was higher tree diversity and more intact forest cover. 31 Habitat fragmentation and homogeneity are common features of urban landscapes and they may mediate the effects of exotic plants on insect herbivores.…”
Section: Introductionmentioning
confidence: 99%